Electronic Archives at KOPDIT Gentiaras as an Effort to Improve Administrative Governance - Rahma Putri, Elox Pradita; Trisnawati, Trisnawati (YHMM PUBLISHING, 2024)
The development of the e-archive system at KOPDIT Gentiaras aims to improve the efficiency of data storage and management for cooperative members. Through this digital system, the processes of recording, searching, and maintaining archives become easier, faster, and more secure from data loss. Data collection methods used in this study include observation, interviews with cooperative administrators, and literature review to strengthen the theoretical foundation. Furthermore, the software development process follows a structured analysis and design approach to ensure the system meets user needs. The results of this development support administrative activities and facilitate comprehensive archive management at KOPDIT Gentiaras, making the cooperative’s operations more effective, accurate, and transparent in serving its members